Pembelajaran Membaca Permulaan Melalui Media Flashcard Untuk Siswa Kelas 1 SDN 31 Mataram - Isna Zuriatni; Intan Permata Hati; Mauliana Gusfian; Mahesa Zanuba Putri; Nanda Nur Sabrina (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
Early reading skills are an important foundation in the learning process in Elementary Schools, especially for first grade students. However, observation results show that there are still students who do not know all the letters of the alphabet and are not able to read simple vocabulary. To overcome this problem, community service activities were carried out in the form of implementing Flashcard learning media designed to support students' early reading skills. The activities were carried out in three stages: observation, planning, and implementation. Flashcard media was designed using the Canva application, printed on HVS paper, and laminated for durability. Flashcards display upper and lower case letters accompanied by pictures and simple words that are familiar to students. The results of the activity showed an increase in the ability to recognize letters and read simple words in first grade students. Students seemed enthusiastic and active in learning, which shows that this media is effective in attracting interest in learning. It is recommended that teachers continue to develop and use learning media that are appropriate to student characteristics, and involve parents to support learning at home.